Comparıson of Athletes’ Excellence Levels Accordıng to Socıo Demographıc Characterıstıcs - Ahmet Uslu, Merve Ferah Tazegül (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Studies show that there is a relationship between sports and perfectionism. Aim: The aim of this study is to compare the perfectionism levels of national athletes according to various variables. Methods: As a data collection tool; ‘’Sports-Specific Multi-Dimensional Perfectionism Scale’’ were used. In the analysis of data in this research, SPSS 20 Package Programme were used. Kolmogorov-Smirnov test were also used in order to determine the distributions of data, and Anova,Homogeneity of Variance’’ test were used to determine homogenity of tests and it was determined that data showed a normal and homogeneous distribution. Descriptive statistics, Independent Sample t test and One Way variance analysis were applied in data analysis. Results: As a result of statistics, in extreme focus on failures sub-dimension, perceived family pressure subdimension and personal standarts sub-dimension male athletes were seen to have higher scores than female athletes. However at the end of comparison of scores related to athletes, there were no statistically significant differences were determined (p>0 ,05). As a result of comparison related to perfectionism dimensions according to marital status, in extreme focus on failures and family pressure sub-dimensions there were statistically significant differences (p<0,05). Conclusion: It has been determined that the level of perfectionism in athletes varies depending on gender. It is also known that sports affect the level of perfectionism positively.